Probabilistic diagnosis of bipolar affective disorder: possibilities and limitations (literature review) - G. G. Simutkin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The literature review presents the main modern data on the epidemiology and socio-economic significance of bipolar affective disorder (BD), discusses the difficulties of early diagnosis of bipolar spectrum disorders, predictors of the bipolar course of affective disorders and a probabilistic approach to the diagnosis of BD, discusses controversial issues in the diagnosis of mixed affective states, the use of potential biomarkers both for the diagnosis of bipolar disorder and for the differential diagnosis of unipolar and bipolar depression, as well as possible therapeutic approaches for the probabilistic diagnosis of bipolar disorder.